ASN Salary Deduction Policy Regulation For UPZ: Between Sharia Compliance and Civil Rights - Muhammad Khusni Alma'arif; Aris Widodo; Roykhatun Nikmah; Eiman Abushihab (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2026)
The salary deduction policy for Muslim civil servants is one way the state facilitates the collection and optimization of professional zakat funds in Indonesia. Legally, regulating the salary deduction policy for civil servants through the payroll system requires a clear legal framework for its implementation and requires an analysis of whether it complies with Islamic law and civil rights. The research method used is a documentation study, a normative legal research type with a descriptive analytical nature. The data sources used are secondary data sources, with primary legal materials in the form of laws and regulations regarding zakat management, as well as secondary legal materials in the form of documents including books, journals, news, fatwas, and relevant research results. The results of the study show that hierarchically the policy of automatic salary deduction for ASN in Law No. 23 of 2011 and Government Regulation No. 14 of 2014 is not explicitly mentioned. Legally, lower legal norms must not conflict with higher norms, but in the implementation of ASN salary cuts, it is only based on a Circular Letter without any higher Regulations that strengthen the ASN salary cut policy. BAZNAS Regulation Number 2 of 2016, if accompanied by a statement of the muzaki's desire, can cause violations due to the failure to fulfill the principle of intention and the principle of pleasure in paying zakat.